High frequency in vitro multiplication of polygonatum verticillatum (l.) All. From rhizome bud explants - Tiwari, Tanuja; Chaturvedi, Preeti (Bangladesh Journal of Botany, 2024)
This work aims to develop a rapid protocol for the in vitro establishment of Polygonatum verticillatum (L.) All., an astounding medicinal herb of Astavarga group of plants. Successful in vitro establishment was achieved utilizing rhizome bud segments of approx. 0.5 to 1.0 cm size as explants. Sterilized explants were cultured on MS medium containing graded concentration of different plant growth regulators used either singly or in various combinations. Maximum (85±10.0%) per cent shoot induction with maximum shoot length (6.50 ± 0.11cm) were recorded in TDZ (2.0 mg/l) + NAA(1.0 mg/l) + GA3 (2.0 mg/l) supplemented MS medium. NAA (1.0 mg/l) + Kn (0.5 mg/l) and IBA(1.0 mg/l) supplemented full strength MS medium with 3% sugar showed highest 70 ± 5.0% rooting response.½ MS+1.5 % sucrose medium augmented with IBA (1.0mg/l) showed the maximum average number of roots per explants (12.8 ± 1.07) with highest root length(6.12±0.27 cm). After hardening plantlets were transferred to pots in glasshouse produced healthy plants with 56% survival rate. Bangladesh J. Bot. 53(1): 203-208, 2024 (March)